2010
DOI: 10.1007/s11274-010-0614-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and metabolic diversity of streptomycetes in pulp and paper mill effluent treated crop fields

Abstract: Irrigation of farm field with water mixed with pulp and paper mill effluent from Century pulp and paper mill in Uttrakhand state of India for over last 25 years in succession increased streptomycetes population (120 9 10 5 ) compared to the fresh water irrigated fields (48 9 10 3 in WIF). Denaturing gradient gel electrophoresis, amplified ribosomal DNA restriction analysis, 16S rRNA gene sequencing, BIOLOG TM substrate usage, production of extracellular enzymes (xylanase and cellulase) and plant growth promoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…The exchangeable Na content of the soils irrigated with the treated pulp and paper effluent was 251 % higher than for the WIF soils. These observations are similar to those observed by Kannan and Oblisami [7] and Tripathi et al [8]. Given the neighbouring location of these 2 fields it is reasonable to believe that the consistent (25 years) of irrigation has been the driver for this observed difference in soil characteristics.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The exchangeable Na content of the soils irrigated with the treated pulp and paper effluent was 251 % higher than for the WIF soils. These observations are similar to those observed by Kannan and Oblisami [7] and Tripathi et al [8]. Given the neighbouring location of these 2 fields it is reasonable to believe that the consistent (25 years) of irrigation has been the driver for this observed difference in soil characteristics.…”
Section: Resultssupporting
confidence: 90%
“…Although several previous studies have investigated the effects of pulp and paper mill effluents on the structure of soil microbial communities, these studies were based solely on biochemical and culture based methods [7,8]. The multiphasic approach combining CLPP, culturable population, and 16S rRNA gene cloning analyses used herein showed an encompassing account and representation of the bacterial response to the pulp and paper irrigation than any single approach could have alone.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the impact of DE irrigation on plant-growth-promoting (PGP) traits and taxonomic composition of soil microbial communities is still poorly understood. Two previous studies have shown that application of industrial effluent to agricultural soils could increase the diversity and catabolic profile of microbial communities [15,16]. However, these studies only considered pulp and paper mill effluent irrigation.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, for our patient the likely source of peritoneal infection was direct inoculation into the peritoneal cavity during paracentesis done in the past. S. viridis is found in the soil in various parts of India (15). (14).…”
mentioning
confidence: 99%